How to improve clotting factors depletion in double‐filtration plasmapheresis. Issue 5 (2nd August 2021) - Naciri Bennani, Hamza; Marlu, Raphael; Terrec, Florian; Motte, Lionel; Seyve, Landry; Chevallier, Eloi; Malvezzi, Paolo; Jouve, Thomas; Rostaing, Lionel; Noble, Johan
Abstract: Background: Double‐filtration plasmapheresis (DFPP), a selective therapeutic apheresis, can deplete pathogenic antibodies/substances, but also important coagulation factors. Aim: To determine if the use of a separator filter with different characteristics (CascadefloEC‐50 W) as compared to the reference filter (PlasmafloOP‐08 W) is as efficient in terms of immunoglobulin loss, but can reduce coagulation factor losses and have similar tolerability. Patients/Methods: This is a single‐center prospective study including 14 patients divided into two groups (7 each): that is, group1 = CascadefloEC‐50 W and group2 = PlasmafloOP‐08 W. We measured immunoglobulins, lipid profiles, blood‐cell counts, hemostasis (prothrombin time, activated partial thromboplastin time), coagulation factors, and natural anticoagulants at before and after the first DFPP‐session. Results: In group 1, the loss of coagulation factors was significantly reduced as compared to group 2 for proteins with a molecular weight of >150 kDa: there was, respectively, an average decrease of 70% vs 31% for fibrinogen ( P  = 0.004), 66% vs 21% for factor V ( P  = 2.16e−07), 60% vs 32% for factor XI ( P  = 6.96e−06), 75% vs 17% for XIII‐antigen ( P  = 0.0002), and 47% vs 0% for VWF‐antigen( P  = 0.02). The decrease in post‐session IgG was, on average, 45% in group 1 and 50% in group 2 ( P  = 0.13). Those results remained significant even when adjusted to the treated‐plasma volume and the pre‐DFPP factor values. Conclusion: DFPP, using a CascadefloEC‐50W as a first‐filter, reduces efficiently IgGs similarly to PlasmafloOP‐08W but spares clotting factors.